Pemberdayaan Penyuluh Pertanian Melalui Implementasi Sistem Pemantauan Tanah dan Lingkungan Berbasis IoT: Studi Kasus Badan Penyuluh Pertanian Selaawi Kabupaten Garut - Agusta Ken Nadila, Anindia; Rima Aditya, Bayu; Uwaisy Marchiningrum, Anranur; Qanit Al-Hijran, Muhammad; Bintang Ramadhan, Muhammad; Ginanjar, Yudha (Pengelola Jurnal Politeknik Negeri Ketapang Jl. Rangga Sentap, Dalong Sukaharja, Ketapang 78813. Telp. (0534) 3030686 Kalimantan Barat, 2025)
Agriculture plays a crucial role in supporting a country's food security and economy. In Indonesia, the agricultural sector also has a major influence on inflation, especially through the commodities of rice, cayenne pepper, and red pepper. However, in Garut Regency, the main problem faced is the crop failure of several farming commodities due to farmers' ignorance in effective farmland management. The need for a new approach to improve agricultural knowledge and management arises, and in this context, the development of an IoT-based soil and environment monitoring system is an appropriate solution. Through this technology, agricultural extension workers can access up-to-date and accurate information on farmland conditions, assist in better decision-making, and provide warnings when soil conditions are not optimal